MODIFICAREA COMPONENŢEI CALITATIVE A PROTEINELOR LA CIANOBACTERIA SPIRULINA PLATENSIS CULTIVATĂ ÎN PREZENŢA UNOR COMPUŞI COORDINATIVI AI CR(III) - USM ADMIN (Studia Universitatis Moldaviae: Stiinte reale si ale naturii, 2008)
SDS-electrophoresis of polypeptide chains of total protein fraction obtained from Spirulina cultivated in the presence of Cr(III) coordination compounds have been carried out. New bands with apparent molecular mass 60, 4 kDa and 66, 7 kDa have been detected in the presence of Cr(III) coordination compounds.